Development and validation of a conceptual model of femininity-related intermediate beliefs about alcohol use among female undergraduate students - Sajeepraew Potikul (2022)
The purpose of this study was to validate a new conceptual model of Femininity-Related Intermediate Beliefs about Alcohol use (FIBA) among female undergraduate students (n = 418). The research instruments used for data collection included the newly-constructed Femininity-Related Intermediate Beliefs about Alcohol use Questionnaire (FIBA-Q), the Alcohol Use Questionnaire (Sakulsriprasert, 2014), and the Drinking Problems Scale for College Student (DPS-C) (Sakulsriprasert, 2014). The data were analyzed using descriptive statistics, confirmatory factor analysis, and structural equation models. The results supported the validity of the FIBA model, both the structure of the model (χ² = 196.828, df = 108, χ²/df = 1.822, RMSEA = 0.044, CFI = 0.921, SRMR = 0.060) and its predictive value on alcohol use and alcohol-related problems. The FIBA model explained 40.1 percent of the variance in alcohol use and 37.4 percent in alcohol-related problems. The results of the study provide foundational knowledge that can be applied for developing alcohol harm reduction interventions for young women.